Finite Volume Method Numerical Modelling of the Penstock Flows in Dam Intake Sector Subjected to Varying Operating Conditions with Particle Image Velocimetry Validation - Zahari N.M.; Zawawi M.H.; Ng F.C.; Abas M.A.; Nurhikmah F.; Aziz N.A.; Tung L.H.; Ismail I.N.; Sidek L.M.; Radzi M.R.M. (Penerbit Akademia Baru, 2023)
The formation of vortex and swirling in any flow structures of the hydropower dam is undesirable, as it reduced the performance of turbine as well as lowered the efficiency of hydroelectric power generation. Furthermore, it could lead to the hydraulic losses at the entrance of power intakes, the blockage at the trash racks due to entrain debris and the reduction of the working life of turbines. This paper studied penstocks flows in the dam intake section numerically. The dynamics of penstocks flows at different operating conditions were analyzed to determine the vortex formation. To access the veracity of the current proposed numerical model, a validating study based on the particle image velocimetry (PIV) experiment was conducted. It was found the discrepancy between both numerical and experimental flow velocities is 12%, implying the numerical model is well-validated and the corresponding findings are acceptable. It was found that the vortex was formed in the penstock that located at the lowest level relative to other penstocks. Furthermore, the highest pressure of 4 MPa was recorded at the bottom section of the penstock which observed vortex. This numerical work provided useful insights for the future dam reliability analysis, particularly involving penstocks and intake section. 2021. All Rights Reserved.